2012
DOI: 10.1073/pnas.1203534109
|View full text |Cite
|
Sign up to set email alerts
|

Targeting blood-brain barrier sphingolipid signaling reduces basal P-glycoprotein activity and improves drug delivery to the brain

Abstract: P-glycoprotein, an ATP-driven drug efflux pump, is a major obstacle to the delivery of small-molecule drugs across the blood-brain barrier and into the CNS. Here we test a unique signaling-based strategy to overcome this obstacle. We used a confocal microscopy-based assay with isolated rat brain capillaries to map a signaling pathway that within minutes abolishes P-glycoprotein transport activity without altering transporter protein expression or tight junction permeability. This pathway encompasses elements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
127
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 127 publications
(129 citation statements)
references
References 46 publications
2
127
0
Order By: Relevance
“…Notably, it is reported that S1P 1 -agonism reduces P-glycoprotein (P-gp) transport activity in rodent in situ perfusion experiments (49). In that study, FTY720 was shown to increase brain accumulation of the drugs by its agonistic activity.…”
Section: Discussionmentioning
confidence: 87%
“…Notably, it is reported that S1P 1 -agonism reduces P-glycoprotein (P-gp) transport activity in rodent in situ perfusion experiments (49). In that study, FTY720 was shown to increase brain accumulation of the drugs by its agonistic activity.…”
Section: Discussionmentioning
confidence: 87%
“…Furthermore, extracellular S1P stimulated Abcb1 transport activity via S1P 1 and S1P 3 receptors, and as data not shown, it was mentioned that exogenous S1P did not modulate Abcb1 expression, suggesting differential activities of intracellular SphK1 and extracellular S1P ( 27 ). On the other hand, Cannon et al ( 33 ) and Miller ( 34 ) showed recently that exogenous S1P decreased Abcb1 activity via S1P 1 in isolated mouse brain and spinal cord capillaries, as well as in isolated killifi sh renal proximal tubules, respectively. Because this effect was rapid and reversible, it did not rely on transcriptional regulation, but either on alteration of the transporter turnover number or on traffi cking of the transport protein away from the exterior surface of the luminal plasma membrane ( 33 ).…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, Cannon et al ( 33 ) and Miller ( 34 ) showed recently that exogenous S1P decreased Abcb1 activity via S1P 1 in isolated mouse brain and spinal cord capillaries, as well as in isolated killifi sh renal proximal tubules, respectively. Because this effect was rapid and reversible, it did not rely on transcriptional regulation, but either on alteration of the transporter turnover number or on traffi cking of the transport protein away from the exterior surface of the luminal plasma membrane ( 33 ). In line with this activity, exogenous cell permeable C 2 -ceramide was able to increase cholesterol effl ux to apolipoprotein A-I by increasing the cell surface presence of Abca1 ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…For many drugs, it is a major determinant of drug pharmacokinetics, driving excretion from liver, gut, and kidney and exclusion from tumors and the CNS. We recently found that basal P-glycoprotein transport activity (but not expression) at the blood-brain and blood-spinal cord barriers could be rapidly and reversibly reduced through sphingolipid signaling (Cannon et al, 2012;Cartwright et al, 2013). Transport activity of other ABC transporters is not affected.…”
Section: Introductionmentioning
confidence: 99%